Accuracy and Bias in Vulnerability Perceptions of Partners Undergoing Emotion‐Focused Therapy for Couples. Issue 2 (20th August 2020) - Wiesel, Ido; Shahar, Ben; Goldman, Rhonda N.; Bar‐Kalifa, Eran
Abstract : The primary mechanism of change in emotion‐focused couples therapy (EFT‐C) is described as one partner accessing and expressing vulnerability, with the other partner responding affiliatively, with compassion, acceptance, validation, and support. These interactions are assumed to restructure the negative, rigid interactional cycle that usually brings couples to therapy and helps build a positive emotional bond. The primary aim of this study was to test whether for this process to occur, partners need to accurately perceive their spouse's experiences of vulnerability during therapy. Specifically, it examined the factors (i.e., tracking accuracy, assumed‐similarity bias, and directional bias) shaping partners' perceptions of their spouse's vulnerability and whether accurate perceptions predict positive session outcomes during EFT‐C. Data from 36 couples who took part in the York Emotional Injury Project were analyzed. Following each session, clients reported their own experience of vulnerability as well as their perceptions of their partners' vulnerability. Session outcome was defined as the extent to which clients reported resolution. Using a multilevel Truth and Bias model, the results indicated that partners accurately perceived changes in their spouses' expressions of vulnerability (i.e., significant tracking accuracy). Interestingly, partners' perceptions were also tied to their own expressions of vulnerability (i.e., significant assumed‐similarity bias) and tended to underestimate the level of their partners' vulnerability expressions (i.e., significant negative mean‐level bias). Using a multilevel Response Surface Analysis, we found that accuracy regarding partners' vulnerability was associated with higher levels of resolution. Resumen: El principal mecanismo de cambio en la terapia de pareja centrada en las emociones (EFT‐C, siglas en inglés) se describe como un integrante de la pareja que accede a la vulnerabilidad y la expresa, y el otro integrante de la pareja que responde afiliativamente; con compasión, aceptación, validación y apoyo. Se supone que estas interacciones reestructuran el ciclo interactivo negativo y rígido que generalmente lleva a las parejas a terapia y ayuda a construir un vínculo emocional positivo. El principal objetivo de este estudio fue evaluar si, para que ocurra este proceso, las parejas necesitan percibir con exactitud las experiencias de vulnerabilidad de su cónyuge durante la terapia. Específicamente, analizó los factores (p. ej.: precisión del seguimiento, sesgo de similitud asumida y sesgo direccional) que determinan las percepciones de las parejas de la vulnerabilidad de su cónyuge y si las percepciones exactas predicen resultados positivos en las sesiones durante la EFT‐C. Se analizaron datos de 36 parejas que participaron en el Proyecto de York sobre Daño Emocional (York Emotional Injury Project). Después de cada sesión, los pacientes informaron su propia experiencia de vulnerabilidad así como sus percepciones de la vulnerabilidad de sus parejas. El resultado de la sesión se definió como el grado en el que los pacientes informaron la resolución. Utilizando un modelo multinivel de verdad y sesgo, los resultados indicaron que las parejas percibieron con exactitud los cambios en las expresiones de vulnerabilidad de sus cónyuges (p. ej.: precisión considerable del seguimiento). De modo interesante, las percepciones de las parejas también estuvieron ligadas a sus propias expresiones de vulnerabilidad (p. ej.: sesgo considerable de similitud asumida) y tendieron a subestimar el nivel de las expresiones de vulnerabilidad de sus parejas (p. ej.: sesgo considerable de nivel medio negativo). Utilizando un análisis superficial de respuesta multinivel, descubrimos que la exactitud con respecto a la vulnerabilidad de las parejas estuvo asociada con niveles más altos de resolución. 摘要: 在情感焦点伴侣治疗(EFTC)中主要的改变机制可以具体描述如下：一方更容易表现得脆弱且把脆弱表达出来，而另一方则以亲和的方式回应; 带着怜悯、接纳、给以验证和支持等。这些相互作用被认为重构了原来周而复始的既消极且僵化的相互影响模式，往往是这种周期性的互动方式把伴侣们带到治疗中来，从而帮助其建立积极的情感纽带。本研究的主要目的是为了测试伴侣是否需要在治疗过程中准确地感知到配偶的脆弱经历以促使这种过程的实现。具体来说，它检查了如下因素(例如追踪准确性、假定的相似偏差和方向偏差)塑造伴侣对配偶脆弱性的感知，以及准确的感知是否预测EFT‐C期间的积极会话结果。研究人员分析了参加约克情感伤害项目的36对夫妇的数据。在每次治疗会谈之后，来访者报告了他们自己的脆弱性经历以及他们对其伴侣表现出的脆弱性的看法。疗程结果被定义为来访者自报的解决程度。使用一个多层次的真相和偏见模型得出结果表明，伴侣准确地感知到配偶脆弱性表达的变化（即显著的跟踪准确性）。有趣的是，伴侣的感知也与他们自己的脆弱性表达相关（即显著的假设相似性偏差），并倾向于低估伴侣的脆弱性表达水平（即显著的负平均水平偏差）。通过多层次的反应面分析，我们发现伴侣脆弱性的准确性与较高的解决水平有关。